forestry in the Second Five-Year Plan - Tiwari, K. M. (Indian Forester, 1956)
The work done on schemes of Forest development in the First Five-Year Plan has been reviewed briefly. From statistical data it has been shown that we must have at least 12% more of the total land area of our country under forests to conform to the minimum proportion of land under forests as laid down in the National Forest Policy of India. It has been, therefore, emphasized that in the Second Five-Year Plan we must attempt to increase the nett forest area by bringing in fresh land under forests. An expenditure of Rs. 100 crores in the Second Five-Year Plan has been envisaged. Vast direct advantages and immense indirect benefits of this socialistic scheme have then been enumerated.